The do's and don'ts of hypoglycemia : an everyday guide to low blood sugar, too often misunderstood and misdiagnosed! - Ruggiero, Roberta , 1940- (Frederick Fell, 2006)
Discusses on how to understand and recognise hypoglycaemia.